How many grid-forming converters are needed? – A techno-economic perspective - Guoxuan Cui; Hongyang Jia; Ning Zhang; Fei Teng (iEnergy)
Renewable generation is rapidly increasing and transforming power systems toward “new-type power systems”. The integration of renewable energy resources necessitates a shift from conventional grid-following converters (GFLs) to advanced grid-forming controls. Although grid-forming converters (GFMs) provide grid support and enhance system stability under weak grid conditions, their deployment requires more robust hardware, complex control algorithms and system operation constraints, resulting in planning and operational trade-offs between system stability and cost efficiency. This paper studies the underexplored question of how many GFMs are needed from a techno-economic perspective. The holistic analysis integrates long-term planning, short-term operational strategies and dynamic stability considerations, thereby supporting large-scale renewable integration while ensuring system security and economic benefits.